Relacje produkcji przemysłowej i zanieczyszczeń środowiska. (Próba oceny zmienności w czasie związków przestrzennych w latach 1975 -1981) - Hendel, Małgorzata (Wydział Prawa i Administracji UAM, 1984)
The study attempts at statistical verification of a hypothesis that considerable amounts of pollution destroying geographical environment are present in the districts of a high value of industrial production per sq. km. Statistical information for the system of districts in the years 1976 -1981 was used to verify the hypothesis, it served to assess three functions of linear regression in which the same describing variable is present, the gross industrial production, a role of describing variables is played in turn by values of annual emmission of dusts, gases and wastes. A conclusion of diminishing effectiveness of production processes from the ecological point of view is formulated in consequence of the assessments. Industrial production generates year by year more and more dusts, gases and wastes polluting natural environment, what is causing serious hazards for human life. Grouping of voivodeships characterized by similar level of industrial pollution is accomplished by using the — so called — Wrocław method of taxonomy.
Relations of industrial production and environmental pollution (An attempt to establish time variability of spatiall relations in the years 1975-1981)